Iranian staff nurses' views of their productivity and human resource factors improving and impeding it: a qualitative study - Salsali Mahvash; Nazari Ali; Nayeri Nahid; Ahmadi Fazlollah (BMC, 2005)
Abstract Background Nurses, as the largest human resource element of health care systems, have a major role in providing ongoing, high-quality care to patients. Productivity is a significant indicator of professional development within any professional group, including nurses. The human resource element has been identified as the most important factor affecting productivity. This research aimed to explore nurses' perceptions and experiences of productivity and human resource factors improving or impeding it. Method A qualitative approach was used to obtain rich data; open, semi-structured interviews were also conducted. The sampling was based on the maximum variant approach; data analysis was carried out by content analysis, with the constant comparative method. Results Participants indicated that human resources issues are the most important factor in promoting or impeding their productivity. They suggested that the factors influencing effectiveness of human resource elements include: systematic evaluation of staff numbers; a sound selection process based on verifiable criteria; provision of an adequate staffing level throughout the year; full involvement of the ward sister in the process of admitting patients; and sound communication within the care team. Paying attention to these factors creates a suitable background for improved productivity and decreases negative impacts of human resource shortages, whereas ignoring or interfering with them would result in lowering of nurses' productivity. Conclusion Participants maintained that satisfactory human resources can improve nurses' productivity and the quality of care they provide; thereby fulfilling the core objective of the health care system.